Espacialidade das migrações temporárias de Mirabelenses: implicações na territorialidade local - Fonseca, Gildette Soares (2009)
The temporaries migrations reflect the process of social inequality that prevails in the hidden corners of Brazil, involving the survival of populations of low purchasing power, while the periodic return to the living space (re)create new meanings. This research contemplates reflections on the history of temporaries migrants in Mirabela, county located in the north of Minas Gerais. Our main goal is to know the spatial dimension of these migrations and their working conditions, examining the implications on the territoriality of the space of Mirabela. Thus, we characterized the geographical category place - living space, - connecting it to temporary migration, analyzing the process of settlement of the county, evaluating the socioeconomic- cultural organization of the migrant population and identifying the formation of social networks of migrants and their families. The theoretical referential used contemplated discussions about geographical category place, concepts of temporary migration, identity, employment relationship, de/reterritorialization and social networks. Considering these assumptions, we execute a descriptive exploratory study, using interviews and narratives of migrants life histories, being each one of the twenty fieldworks essential to this research. From the compilation of data, we elaborate maps and chart that show the spatialization of temporaries migrations of the citizens of Mirabela, being these same temporaries migrations also occur in other regions of Minas Gerais and in the states of Bahia, Tocantins, Goiás and Mato Grosso do Sul. In these regions migrants work in the coffee harvest, in coal production, in sugar cane and wood cutting, beyond some of them develop industrial activities during the year in Nova Serrana, county of the state of Minas Gerais, returning to Mirabela only on vacation period and long holidays. We realized that the responsible factors for migrations are the inefficiency of the municipal government to attract investments for the generation of jobs; the neglect of state and federal managers with the north of Minas Gerais counties, specifically Mirabela; the absence of public policies aimed at setting the man on the field, since the majority of the migrant population has few years of study and performing agricultural activities; and the powerlessness of governments in taking care of the interests of migrants workers. In this scene we observe that there is economic stagnation - low purchasing power - therefore, many young people without work perspective follow the path of parents and grandparents, occurring irrecoverable losses in the familiar scope and in the living space, - de/re-territorialization - thence migrants seek to places that most resemble their dogma/realities and attempt in a closing and confining process to form their territories, as the Santo Hipólito Settlement, which shelters families who left the rhythm of migration during the agricultural harvests and opted to live of the subsistence, however with better quality of life. We also realize the development of networks of solidarity between migrants and their families face to the difficulties confronted in the workplaces and in Mirabela